2019
DOI: 10.1177/1753193418822425
|View full text |Cite
|
Sign up to set email alerts
|

Universal 2 total wrist arthroplasty for the salvage of failed Biaxial total wrist arthroplasty

Abstract: Universal 2 implants may be an alternative to total wrist arthrodesis for the salvage of failed Biaxial total wrist prostheses. We assessed 40 Universal 2 revision implants retrospectively. Fourteen of these wrists were converted to total wrist arthrodeses, and two wrists received a third total wrist arthroplasty after a mean period of 5.5 years. Twenty-four of the Universal 2 implants that remained in situ after a mean follow-up of 9 years (range 4 to 13 years) were re-examined. Sixteen functioned satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, none of these studies report osteolysis mimicking a neoplasm or mention the formation of a pseudotumor. [12][13][14] In a recent study, Fischer et al described a radiologic tumor-like presentation of periprosthetic osteolysis after TWA is mentioned. 15 Although they did not formally mention a pseudotumor, the radiographs are similar to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies report osteolysis mimicking a neoplasm or mention the formation of a pseudotumor. [12][13][14] In a recent study, Fischer et al described a radiologic tumor-like presentation of periprosthetic osteolysis after TWA is mentioned. 15 Although they did not formally mention a pseudotumor, the radiographs are similar to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…One case series of 40 revision total wrist arthroplasties reported 60% implant survival at 9 years. 13 A 2018 retrospective review of 18 patients who underwent revision total wrist arthroplasty found 5-year implant revision survivorship to be 83%. 14 A similar retrospective review of 16 patients found that revision arthroplasty of the wrist is a valid option for failed primary total wrist arthroplasty if the goal is to preserve motion.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported procedure for a failed total wrist arthroplasty is conversion to a total wrist arthrodesis, but this procedure is challenged by loss of bone stock and poor bone quality, which is typical following a failed total wrist arthroplasty. 13,14 However, with employment of sound surgical technique incorporating necessary bone grafting principles and sufficient internal fixation, successful conversion is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on long-term results are less frequent, although the publications have increased [10][11][12]. For rheumatics, the precarious bone situation with early onset of osteoporosis and the associated loss of bone mass and accompanying pathologies of the periarticular tissues limits the conditions for the long-term success of a wrist prosthesis [13][14][15]. Considering the worst-case scenario, the survival rate of the prosthesis after 6.9 years was 44%.…”
Section: Discussionmentioning
confidence: 99%